Prenatal diagnosis of fetuses with 15q11.2 BP1-BP2 microdeletion in the Chinese population: a seven-year single-center retrospective study - Jianlong Zhuang; Na Zhang; Wanyu Fu; Yuying Jiang; Yu’e Chen; Chunnuan Chen (Molecular Cytogenetics, 2024)
Abstract Background The 15q11.2 BP1-BP2 microdeletion syndrome is associated with developmental delays, language impairments, neurobehavioral disorders, and psychiatric complications. The aim of the present study was to provide prenatal and postnatal clinical data for 16 additional fetuses diagnosed with the 15q11.2 BP1-BP2 microdeletion syndrome in the Chinese population. Methods A total of 5,789 pregnancy women that underwent amniocentesis were enrolled in the present study. Both karyotype analysis and chromosomal microarray analysis (CMA) were conducted on these subjects to detect chromosomal abnormalities and copy number variants (CNVs). Whole exome sequencing (WES) was performed to investigate sequence variants in subjects with clinical abnormalities after birth. Results Sixteen fetuses with 15q11.2 BP1-BP2 microdeletion were identified in the present study, with a detection rate of 0.28% (16/5,789). The 15q11.2 BP1-BP2 microdeletion fragments ranged from 311.8 kb to 849.7 kb, encompassing the NIPA1, NIPA2, CYFIP1, and TUBGCP5 genes. The follow-up results regarding pregnancy outcomes showed that five cases opted for pregnancy termination, while the remaining cases continued with their pregnancies. Subsequent postnatal follow-up indicated that only one case with the 15q11.2 BP1-BP2 microdeletion displayed neurodevelopmental disorders, demonstrating an incomplete penetrance rate of 9.09% (1/11). Conclusion The majority of fetuses with the 15q11.2 microdeletion exhibit typical features during early childhood, indicating a low penetrance and mild impact. Nonetheless, pregnancies involving fetuses with the 15q11.2 microdeletion require thorough prenatal counseling. Additionally, enhanced supervision and extended postnatal monitoring are warranted for those who choose to proceed with their pregnancies.